Curricular integration for the achievement of education from the perspective of integral training in a professional education school in Ceará (Olhar de Professor, 2022)
This article aims to reflect on the relevance of curricular integration from the perspective of comprehensive training in a Professional Education school in the state of Ceará. To that end, it investigates how this integration takes place between the technical and regular bases, and how it has developed considering the integrality of the training of teenager served by this type of education. As it is a case study with a qualitative bias, it uses structured interviews as a research instrument, which were conducted with 5 teachers, 7 students, 3 coordinators and 1 school principal. From the results of the research, the distance between general basic education and professional education is evident, with this duality remaining. It is perceived a difficulty in implementing an Integrated Professional Education that is effective in the sense of this articulation, so that the subject is trained in its broad physical, intellectual and technological capacity. This distance makes it difficult to integrate the curriculum and work with these students from the perspective of comprehensive training. The need arises to think of strategies and practices that expand this integration, primarily through the study of the curricula of courses offered by the institution and pedagogical meetings for integration between the professional and regular axes.
Keywords: Curricular integration. Integral training. Professional education.